Toxins Secreted by Bacillus Isolated from Lung Adenocarcinomas Favor the Penetration of Toxic Substances - Merlos, Alexandra; Rodríguez, Pau; Bárcena-Uribarri, Iván; Winterhalter, Mathias; Benz, Roland; Vinuesa, Teresa; Moya, Juan A.; Viñas, Miguel (Frontiers in Microbiology, 2015)
The aim was to explore the eventual role of bacteria in the induction of lung cancer by smoking habits. Viable bacteria closely related to the genus Bacillus were detected at high frequencies in lung-cancer biopsies. Similar, if not identical, microbes were isolated from cigarettes and in smog. Bacteria present in cigarettes could be transferred to a physiological solution via a "smoker" device that mimicked their potential transfer during smoking those bacteria produce exotoxins able to open transmembrane pores. These channels can be used as a way to penetrate cells of benzopyrenes and other toxic substances present in tobacco products. We hypothesize that Bacillaceae present in tobacco play a key role in the development of lung cancer.